Abu Bakr Ibn Mujahid dan Qirâ’ah Sab’ah - Nurhidayah, Lilik; Majid, Andi Muhammad Sultan Maulana (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The problem in this research is the misunderstanding of some of the general public about the meaning of the hadith (seven) of the prophet sallallaahu 'alaihi wasallam. The purpose of this study is to analyze the reasons that prompted Ibn Mujahid to collect seven qirâ`ât in his book "Al-Sab'ah". This research also uses the library research method, namely research by examining written sources, such as books or books related to the subject matter of Ibn Mujahid. From the results of this study it was found that the correct meaning of the hadith (seven) namely the seven language dialects also ibn mujahid had three reasons that prompted him to collect seven qirâ`ât. The conclusions of this study are, firstly, the correct meaning of the hadith (seven) are seven dialects of language, secondly, Ibn Mujahid has three main reasons for collecting the purpose of qirâ`ât, namely the number of qirâ`ât, so that the qirâ`ât of the imams is easy to obtain and learn, preserve and maintain qirâ`ât.